Implementing Enhanced AODV Using FLAP in Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2017)
Wireless sensor networks (WSN), sometimes called wireless sensor and actuator networks (WSAN), are spatially distributed autonomous sensors to monitor physical or environmental conditions, such as temperature, sound, pressure etc. and to cooperatively pass their data through the network to a main location. AODV is a reactive protocol that has one section per destination. It uses RREQ & RREP to identify routes. It takes a long time to setup routes which reduces efficiency of the protocol. The amount of time required in handoffs can be reduced using FLAP protocol with AODV. Reducing Handoffs will help in increasing throughput and battery life of the network. This paper focuses on the enhanced AODV protocol with FLAP .Comparison of various protocols with enhanced protocol is shown through NS2 simulation by using parameters Throughput, Packet Delivery Ratio and Delay Time.